The Future of Philippine Agriculture under a Changing Climate : Policies, Investments and Scenarios - Agcaoili-Sombilla, Mercedita C. (Mercedita Castro); Rosegrant, Mark W. (Book collections on Project MUSE., 2019)
The Philippine economy has grown rapidly since 2010, but despite this growth, poverty and inequality remain high. Two-thirds of the poor live in rural areas, and the weak performance of the agriculture sector has contributed to the slow improvement in livelihoods. The challenge for agriculture will further increase, with climate change posing a growing threat to the sector. But agricultural transformation to spur sustained growth and reduce poverty is still possible under climate change with aggressive institutional reforms and implementation of the right mix of policies and programmes. The identification of the suitable policy and programme combination requires an accurate assessment of the key drivers of agricultural growth and food security; the impacts of climate change on agriculture and the overall economy; and the effectiveness of policies for adaptation and growth. This book addresses these big issues, focusing on enhancing the adaptation capacity of the Philippine agriculture sector. It is designed to provide a much-needed base of knowledge and menu of policy options to support decision- and policymaking on agriculture, climate change, and food security. The volume uses newly generated data, modelling outputs, and innovative analyses to provide a scientific basis for a variety of adaptation measures under different sets of climate change scenarios to guide decision-makers in strategic planning and policy formulation. "As we have actually experienced in Leyte, an island province in the Visayas where Super Typhoon Yolanda (Haiyan) struck, disasters caused by natural hazards could completely negate economic gains, devastate families and shatter dreams. Our greatest challenge is to make ourselves better prepared for and be more resilient to such disasters. Natural hazards need not always lead to loss of so many lives and properties. This book shows us ways and provides tools to draw up climate change and socioeconomic scenarios at the regional and provincial levels, allowing us to identify strategies for mitigating climate change risks." -- Ernesto M. Pernia, Secretary of Socioeconomic Planning, National Economic and Development Authority, Philippines "This book by top Philippine researchers combines state-of-the-art biophysical and economic modeling of climate impacts and adaptation policies with in-depth synthesis of agriculture, natural resources, climate trends, and policies. It provides a comprehensive assessment of climate change impacts on agriculture and the broader economy to provide important insights for Philippine policymakers." -- Dr Cynthia Rosenzweig, Head, Climate Impacts Group, NASA Goddard Institute for Space Studies and Co-Founder of the Agricultural Model Inter-comparison and Improvement Project (AgMIP)